2019
DOI: 10.1093/icb/icz025
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria and the Origin of Species: Bridging Genetic and Ecological Perspectives on Speciation Processes

Abstract: Mitochondria have been known to be involved in speciation through the generation of Dobzhansky–Muller incompatibilities, where functionally neutral co-evolution between mitochondrial and nuclear genomes can cause dysfunction when alleles are recombined in hybrids. We propose that adaptive mitochondrial divergence between populations can not only produce intrinsic (Dobzhansky–Muller) incompatibilities, but could also contribute to reproductive isolation through natural and sexual selection against migrants, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 140 publications
1
24
0
Order By: Relevance
“…Additionally, population genetics studies from species and different population isolates from the same species in the copepod Tigriopus californicus (Burton et al, 2006;Ellison and Burton, 2006), in reptiles (chameleons) ( Bar-Yaacov et al, 2015) and in birds (sparrows) (Trier et al, 2014), revealed hybrid incompatibility, which constitutes an important step toward speciation. These pieces of evidence provide strong support for the importance of genetic compatibility between the nuclear and mitochondrial genomes, that when interfered with can either lead to diseases (Gershoni et al, 2014) or lead to the creation of reproductive barriers in both invertebrates and in vertebrates (Gershoni et al, 2009;Trier et al, 2014;Telschow et al, 2019;Tobler et al, 2019). The underlying mechanism of mito-nuclear genetic compatibility has previously been thoroughly discussed at the protein-protein, RNA-protein and protein-mtDNA levels at the whole organism level (Bar-Yaacov et al, 2012;Levin et al, 2014;Hill, 2019;Hill et al, 2019).…”
Section: Mito-nuclear Interactions: Corresponding Signatures Of Selecmentioning
confidence: 85%
“…Additionally, population genetics studies from species and different population isolates from the same species in the copepod Tigriopus californicus (Burton et al, 2006;Ellison and Burton, 2006), in reptiles (chameleons) ( Bar-Yaacov et al, 2015) and in birds (sparrows) (Trier et al, 2014), revealed hybrid incompatibility, which constitutes an important step toward speciation. These pieces of evidence provide strong support for the importance of genetic compatibility between the nuclear and mitochondrial genomes, that when interfered with can either lead to diseases (Gershoni et al, 2014) or lead to the creation of reproductive barriers in both invertebrates and in vertebrates (Gershoni et al, 2009;Trier et al, 2014;Telschow et al, 2019;Tobler et al, 2019). The underlying mechanism of mito-nuclear genetic compatibility has previously been thoroughly discussed at the protein-protein, RNA-protein and protein-mtDNA levels at the whole organism level (Bar-Yaacov et al, 2012;Levin et al, 2014;Hill, 2019;Hill et al, 2019).…”
Section: Mito-nuclear Interactions: Corresponding Signatures Of Selecmentioning
confidence: 85%
“…While the coevolution of mitochondrial and nuclear genomes does occur, the unique biology of mitochondria complicates our view of a species' evolutionary history [32][33][34][35][36][37][38]. In most metazoans, uniparental inheritance, lack of recombination and high mutation rate of mtDNAs make it difficult to separate the effect of genetic drift from natural selection [39].…”
Section: Introductionmentioning
confidence: 99%
“…I also consider a potentially pivotal role played by recombination of mitochondrial chromosomes in the generation of mt DNA barcode gaps. I propose that a better understanding of the evolutionary mechanism that generates the genetic structure of mt DNA across eukaryotes is critical not only with regard to assessing the value of DNA barcodes as a tool in taxonomy (Baker, Tavares, & Elbourne, 2009; Rubinoff, Cameron, & Will, 2006) but also for a better understanding of the process of speciation (Hill, 2016; Sunnucks, Morales, Lamb, Pavlova, & Greening, 2017; Tobler, Barts, & Greenway, 2019).…”
Section: Introductionmentioning
confidence: 99%